Gerhard Richter : The Daily Practice of Painting : Writings and Interviews 1962-1993 - Anthony d'Offay Gallery, London; Britt, David; Buchloh, Benjamin H.D.; Corà, Bruno; Dienst, Rolf-Gunter; von Drathen, Doris; Grüterich, Marlis; Haase, Amine; Hülsmann, Dieter; Obrist, Hans-Ulrich; Pehnt, Wolfgang; Polke, Sigmar; et al. (London : Thames and Hudson London, 1995)
Gerhard Richter is one of the foremost painters of his generation. A great deal has been written about the bewildering heterogeneity of his work over the past thirty years, his seemingly wilful and defiant movement between abstract and figurative modes of representation and his use of a variety of methods of applying paint to canvas. Central to his work is a strong set of values which throughout his career he has expressed in extensive notes and writings, and in provocative and memorable public declaration in which he shows himself the master of the paradoxical statement. Over seven years in preparation, this book makes available a selection of Richter's texts, many translated for the first time. these texts come from all periods of his career : letters and interviews, public statements about specific exhibitions private reflections drawn from personal correspondence ; answers to questions posed by critics ; and excerpts from journals discussing the intentions, subjects, methods and sources of his works from various periods. Accompanied by biographical photographs from the artist's personal collection, these texts form a brilliantly iluminating commentary on Richter's art, as well as providing a thought-provoking discussion on the status of art in society today.
bibliog. p. 278-282
biog. p. 274-277
Engels
boek
Keywords: Richter, Gerhard